Study on Dynamic Injection Prediction Model of High-Pressure Common Rail Injector under Thermal Effect - Zhenming Liu; Ziming Li; Jiechang Wu; Jingbin Liu; Ping Chen (Energies, 2022)
This study investigates a prediction model for the cycle injection quantity in a high-pressure common rail injector under a transient thermal boundary. The results show that the transient temperature increase curve calculated by the mathematical model of the common rail injector under adiabatic flow is significantly different from the experimental data. A non-isothermal model of the injector coupled with heat transfer is established, which considers the actual heat transfer phenomenon. The excellent agreement between the new calculation results and the experimental data confirms that the fuel injection process of a common rail injector comprises the coupled phenomena of fuel heating and heat transfer. Based on the established simulation model, it is found that in the continuous injection process of the injector, owing to the thermal effect of injection, the cycle injection quantity decreases gradually with an increase in the injector working time and then stabilizes. Under the condition of an injection pulse width of 1.2 ms and frequency of 100 Hz, when the injection pressure increases from 140 MPa to 300 MPa, the reduction in the cycle injection quantity increases from 3.9% to 7.8%, because the higher injection pressure results in higher transient heat at the nozzle holes. In the work of common rail injector assemblies, to achieve more accurate control of the cycle injection quantity, it is necessary to include the correction of a decreasing cycle injection quantity caused by transient heat in the electronic control system.